2012
DOI: 10.1016/j.ijhydene.2012.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical reliability and durability of SOFC stacks. Part I : Modelling of the effect of operating conditions and design alternatives on the reliability

Abstract: Creep Contact analysis a b s t r a c tElectrochemical and mechanical aspects in solid oxide fuel cell stack must be understood to meet the reliability targets for market implementation. This study presents a stack modelling framework that combines thermo-electrochemical models, including degradation and a contact finite-element thermo-mechanical model. It considers rate-independent plasticity and creep of the component materials and proposes periodic boundary conditions to model the stacking of repeating units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 54 publications
0
55
0
Order By: Relevance
“…Our structural analyses [27,28] have furthermore shown that all these manipulations can be opposite to those that promote mechanical reliability and durability, resulting in trade-offs between electrochemical and mechanical considerations. Fig.…”
Section: Lifetime Improvementmentioning
confidence: 93%
See 3 more Smart Citations
“…Our structural analyses [27,28] have furthermore shown that all these manipulations can be opposite to those that promote mechanical reliability and durability, resulting in trade-offs between electrochemical and mechanical considerations. Fig.…”
Section: Lifetime Improvementmentioning
confidence: 93%
“…The lack of knowledge on mechanical failures in SOFC stacks, and the variety of their nature, prevent their simplification to indicators, hence simple implementation in the optimisation problem. For future structural analysis [27,28], discrete values of the decision variables that mainly govern the temperature profile in an SRU embedded in a stack are enforced, within the typical range for intermediatetemperature, anode-supported SOFCs:…”
Section: Investigated Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Part I [46] focuses on the influence of the SOFC stack operation parameters on the mechanical reliability, whereas this Part II investigates the combined or separate effects of electrochemical and mechanical degradation on the structural reliability of a planar stack with anode-supported cell. The analysis encompasses rate-independent plasticity and creep deformation of the components and shrinkage of the anode material, together with electrochemical degradation to gain knowledge on the detrimental phenomena acting during combined steady-state operation, performance characterisation and thermal cycling, under practical operating conditions.…”
Section: Introductionmentioning
confidence: 99%